1994
DOI: 10.1073/pnas.91.17.7907
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide inhibition of acetylcholinesterase gene expression induces progenitor cell expansion and suppresses hematopoietic apoptosis ex vivo.

Abstract: To examine the role of acetylcholinesterase (EC 3.1.1.7) in hematopoietic cell proliferation and differentiation, we administered a 15-mer phosphorothioate oligonucleotide, antisense to the corresponding ACHE gene (AS-ACHE), to primary mouse bone marrow cultures. Within 2 hr of AS-ACHE addition to the culture, ACHE mRNA levels dropped by approximately 90%, as compared with those in cells treated with the "sense" oligomer, S-ACHE. Four days after AS-ACHE treatment, ACHE mRNA increased to levels 10-fold higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 31 publications
3
53
0
1
Order By: Relevance
“…[4][5][6] AChE is also expressed in the hematopoietic system, within megakaryocytes and erythrocytes, where it is suspected to play a role in hematopoiesis. 7,8 While human megakaryocytes have low-and erythrocytes high-AChE expression, the reverse situation is present in rodents, where AChE is strongly expressed in megakarocytes but is essentially absent from erythrocyes. 9 It was recently reported that AChE was also expressed during apoptosis induced by a variety of agents in different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] AChE is also expressed in the hematopoietic system, within megakaryocytes and erythrocytes, where it is suspected to play a role in hematopoiesis. 7,8 While human megakaryocytes have low-and erythrocytes high-AChE expression, the reverse situation is present in rodents, where AChE is strongly expressed in megakarocytes but is essentially absent from erythrocyes. 9 It was recently reported that AChE was also expressed during apoptosis induced by a variety of agents in different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects of acetylcholine on stem cell proliferation are indicated by the positive effects of antisense oligonucleotides for AChE on proliferation and expansion of progenitor cells in bone marrow cultures (27).…”
Section: Morphogenetic Celi Movements In Early Embryosmentioning
confidence: 99%
“…But the full picture is more complex, since AChE also occurs in nonneural and embryonic tissues like red blood cells, megakaryocytes, and migrating neural crest cells (Brimijoin & Koenigsberger, 1999). Proposed noncholinergic roles for AChE range from neuromodulation by secreted forms to promotion of cell proliferation in tumor growth and hematopoiesis (Soreq et al, 1994). Prenatal exposure to organophosphate and carbamate pesticides could have adverse effects on neural development by interfering with the morphogenic function of AChE.…”
Section: Wwwintechopencommentioning
confidence: 99%